2019
DOI: 10.5194/amt-12-5547-2019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MOPITT Version 7 joint TIR–NIR X<sub>CO</sub> retrievals with TCCON

Abstract: Abstract. Observations of carbon monoxide (CO) from the Measurements Of Pollution In The Troposphere (MOPITT) instrument aboard the Terra spacecraft were expected to have an accuracy of 10 % prior to the launch in 1999. Here we evaluate MOPITT Version 7 joint (V7J) thermal-infrared and near-infrared (TIR–NIR) retrieval accuracy and precision and suggest ways to further improve the accuracy of the observations. We take five steps involving filtering or bias corrections to reduce scatter and bias in the data rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…The urban regions often have different surface parameters (e.g., surface temperature and emissivity) and usually but not always have higher CO concentrations than non-urban regions. However, the surface parameters are unlikely to impact the ultimate quality of MOPITT retrieval products (Pan et al, 1998;Ho et al, 2005). The goal of this study is to understand if MOPITT retrievals are able to represent conditions over urban regions given sampling and cloud cover.…”
Section: Aircraft Measurements Used For Comparisonsmentioning
confidence: 99%
“…The urban regions often have different surface parameters (e.g., surface temperature and emissivity) and usually but not always have higher CO concentrations than non-urban regions. However, the surface parameters are unlikely to impact the ultimate quality of MOPITT retrieval products (Pan et al, 1998;Ho et al, 2005). The goal of this study is to understand if MOPITT retrievals are able to represent conditions over urban regions given sampling and cloud cover.…”
Section: Aircraft Measurements Used For Comparisonsmentioning
confidence: 99%
“…In addition to the different instrument sensitivities, however, there is also a known problem in the TCCON X CO scaling, wherein the TCCON data were scaled down by ≈6.7% to match older aircraft data. There is now less confidence placed in this value given that it has changed as more recent in situ profiles have been added for comparison [62], and thus it is believed that this scaling factor also contributes to the observed discrepancy between the NUCAPS and TCCON CO. Figure 6. Box-whisker robust error statistics (%) of total column SNPP NUCAPS trace gas retrievals (QA-accepted cases including trace gas QA) versus means at individual collocated (∆r ≤ 125 km and ±2 h) TCCON stations, ordered from south to north: (left) CO, (center) CH 4 , and (right) CO 2 .…”
Section: Statistical Analysis Versus Tccon Baselinementioning
confidence: 99%
“…6. The KORUS-AQ campaign provides a unique test bed for comparing surface and aircraft in situ observations with ground-based and satellite-based remote sensing (Herman et al, 2018), particularly important for targeted short-lived species such as formaldehyde (CH 2 O) and nitrogen dioxide (NO 2 ). Miyazaki et al (2019a) showed that the background Figure 1.…”
Section: Introductionmentioning
confidence: 99%